Surfactant-free synthesis of three-dimensional nitrogen-doped hierarchically porous carbon and its application as an electrode modification material for simultaneous sensing of ascorbic acid, dopamine and uric acid. Issue 3 (17th January 2017) - Nsabimana, Anaclet; Lai, Jianping; Li, Suping; Hui, Pan; Liu, Zhongyuan; Xu, Guobao
Abstract : A 3D N-doped hierarchically porous carbon modified electrode enables simultaneous sensitive detection of ascorbic acid, dopamine and uric acid. Abstract : Three-dimensional N-doped hierarchically porous carbon (3D NHPC) was synthesized successfully without using any surfactant or etching agent. This simple and effective synthesis method was accomplished by solvothermal synthesis followed by pyrolysis. The physical morphology and chemical composition of 3D NHPC were verified by scanning electron microscopy, nitrogen adsorption–desorption, and X-ray photoelectron spectroscopy. Its structural studies reveal that it exhibits a micro–mesoporous hierarchical structure and contains C, O and N atoms forming different functional groups. The characterization also reveals that 3D NHPC has a Brunauer–Emmett–Teller (BET) surface area of 594.774 m 2 g −1 and the micropore volume was calculated to be 0.192 cm 3 g −1 using the t -plot method. Its catalytic activity was investigated by studying its application for simultaneous determination of ascorbic acid (AA), dopamine (DA) and uric acid (UA) by cyclic voltammetry and square-wave voltammetry at physiological pH. A 3D NHPC-modified glassy carbon electrode exhibits linear ranges from 0.05 to 14.50 μM, 1.0 to 120.0 μM, and 2.0 to 30.0 μM for DA, AA and UA, respectively. It also exhibits low detection limits (0.02, 0.10, and 0.14 μM for DA, AA, and UA, respectively), good reproducibility and stability. The urine sample analysis results show good recoveries ranging between 96.30% and 105.40%.